2019
DOI: 10.1111/ggi.13595
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of risk behaviors in Brazilian older adults: A latent class analysis

Abstract: Aim The aim of the present study was to describe the clustering of diet, physical activity, television viewing, and tobacco and alcohol use among Brazilian older adults (aged ≥60 years). Methods We carried out a secondary analysis of the Brazilian National Health Survey of 2013. Brazilian older adults (n = 11 177) reported their consumption of fruit and vegetables, leisure physical activity, television viewing, tobacco smoking, and alcohol intake. Latent class analysis was used to identify behavior patterns. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
2
5
0
1
Order By: Relevance
“…Regarding health behaviors, the results of this study showed a lower consumption of fruits and vegetables among individuals who smoked at the time of the interview and former smokers. These results are consistent with previous studies 44 , 45 demonstrating an agglutination of behaviors that characterize a healthy lifestyle, such as the consumption of fruits and not smoking. Thus, these findings demonstrate the importance of planning joint actions to increase the fruits and vegetables consumption since a healthy habit can potentially influence others.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding health behaviors, the results of this study showed a lower consumption of fruits and vegetables among individuals who smoked at the time of the interview and former smokers. These results are consistent with previous studies 44 , 45 demonstrating an agglutination of behaviors that characterize a healthy lifestyle, such as the consumption of fruits and not smoking. Thus, these findings demonstrate the importance of planning joint actions to increase the fruits and vegetables consumption since a healthy habit can potentially influence others.…”
Section: Discussionsupporting
confidence: 93%
“…Our study findings align with previous research conducted among general adult populations 7,9,41 . The existing literature indicates that the most prevalent clusters of health behaviors among adults involve low fruit and vegetable intake combined with low physical activity, as well as alcohol drinking and smoking.…”
Section: Discussionsupporting
confidence: 90%
“…Our study findings align with previous research conducted among general adult populations. 7 , 9 , 41 The existing literature indicates that the most prevalent clusters of health behaviors among adults involve low fruit and vegetable intake combined with low physical activity, as well as alcohol drinking and smoking. Specifically, the highest prevalence, ranging from 47% to 54%, was observed for the cluster characterized by “low fruit and vegetable intake and low physical activity.” Furthermore, the prevalence ratios were highest for alcohol use and smoking, ranging from 1.89 to 2.89.…”
Section: Discussionmentioning
confidence: 99%
“…This distinction may be attributed to the setting and context of the study. Additionally, the variation in results could be attributed to the fact that women tend to be more cautious about their health [51], which…”
Section: Discussionmentioning
confidence: 99%